Best practices in safety management for conventional civil construction industry in Malaysia [compact disc] - 335663 Rosli Ahmad; Abdul Rahim Abdul Hamid, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2008